DESIGN AND IMPLEMENTATION OF A WEB-BASED STUDENT SAVINGS MANAGEMENT SYSTEM USING THE AGILE METHOD - Reni Haerani; Shopi Nurul Hasanah; Sefta Tri Wahyuni; Melinne Maldini Rosady (Universitas Serang Raya, 2026)
The implementation of a web-based student savings information system created with the Agile methodology is covered in this study. This approach is intended to assist schools in more effectively and transparently managing student savings. The purpose of this method is to assist schools in more effectively and openly managing student savings. The Agile approach method is used in the information system design; the development process is broken up into iterative sprints that enable ongoing improvement based on input from stakeholders. for kids, parents, and school officials, this system offers features like savings contributions, withdrawals, transaction history, and user account management. Agile makes it possible to build useful, user-friendly apps in a comparatively short development cycle by improving communication between the development team and users. The final findings demonstrate how well the Agile methodology supports the development of an educational financial system that calls for adaptability, reactivity, and ongoing user involvement. A website-based student savings information system that may enhance the efficacy and efficiency of finding, generating, and storing student saving data is the result of this study. Keywords: Student Savings; Agile Methods; Information System; Data Management; Web Application;